If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12=x/9
We move all terms to the left:
-12-(x/9)=0
We add all the numbers together, and all the variables
-(+x/9)-12=0
We get rid of parentheses
-x/9-12=0
We multiply all the terms by the denominator
-x-12*9=0
We add all the numbers together, and all the variables
-1x-108=0
We move all terms containing x to the left, all other terms to the right
-x=108
x=108/-1
x=-108
| 23n-24=252 | | 4x=-3x+49 | | 4x²-11x=74 | | 2.5-0.03x=0.43 | | 3(-3y+1)+3y=-15 | | x+48+x+74+68=180 | | 4(x+3)=10x-9 | | 3(-3+1)+3y=-15 | | 140+x22=18 | | x*(20-2x)*(30-2x)=1009 | | 19x+56=19x+23 | | 3(x-5)+x=4x-15 | | -2(-4x-1)-x+3=x+3=−30 | | x+3+x+3=- | | 4x+550=15x | | x+47+x+57+80=180 | | -2=1/2(10k-16)+11 | | 2x+89=871 | | 15c-2c-11c=18 | | 8m2-7=193 | | 4(x+5)-6(x-2)=26 | | -2(-4x-1)-x+3=−30 | | 12h-10h=10 | | n/5=1 | | 2(4k-6)=8k-12 | | 2(x+5)=3(2-5x) | | (6k-6)=(-8k+22) | | 2-5x=3(2-3x | | 2-2y-10y+13=27 | | 15h-9h-h-3h=20 | | 5x+2x=4x-3 | | f(2)=6+5=11 |